Verification of Copernicus riparian zones local component for Bulgaria – specific cases and typical problems - Yulia G. KROUMOVA; Radka G. KOLEVA; Youlin N. TEPELIEV; Ventzeslav N. DIMITROV (European Journal of Geography)
This paper deals with quantitative evaluation of Riparian zones land cover and land use data set for Bulgaria, supported by Copernicus Programme's funds. This verification task is a part of a project of the European Environmental Agency. The methodology is based on visual inspection of sample polygons on top of reference data sets. The web-based LACO-Wiki tool is used for the verification, based on levels 1 to 4 of MAES (Mapping and Assessment of Ecosystems and their Services) nomenclature. Typical class encoding errors and delineation drawbacks are grouped and analysed as several problem types. Detailed scores and accuracy estimates are provided, supported by appropriate visual examples. Class code confusion appears mostly in classes missing or with rare occurrence in Bulgaria. In general, the delineation is correct with some predominance of unnecessary parts inclusion in the sample polygons area. The Riparian zones product provides very good thematic and spatial detail and can be of value for many applications